Literature study: potential of additional technology on conventional motorcycles on reducing the impact of exhaust gas emissions on the environment - Waskitho, Wiji Ninggar; Afif, Ahmad Fauji; Wijaya, Alfin Cakra; Alvian Nurdiansyach, Muhammad; Hidayatulloh , Putra Ragil; Arianto, Faiz Daffa (JMEL : Journal of Mechanical Engineering Learning, 2024)
Motorbikes in Indonesia reached 125,305,332 units or 84.5% of total motorized vehicles. Indonesia ranks 26th in the country with the highest level of air pollution in the world. Motor vehicles produce 70-80% air pollution and industry 20-30%. The CO and HC produced are not good for the environment. Reducing exhaust emissions becomes very important by identifying effective additional technologies. The research method used in this research is the literature review method by collecting information and data using various library materials. The results of the literature review show that the addition of technology can reduce exhaust gas emissions in the form of CO and HC. By adding additional technology to motorbikes, of which there are 125,305,332 units or 84.5%, it can reduce the level of air pollution in Indonesia. The use of additional technology on conventional motorbikes has great potential to reduce exhaust emissions which have a negative impact on the environment, but further research is needed to identify effective and economical technology.